A House with Good Bones - Kingfisher, T. (New York : Nightfire, 2023)
"T. Kingfisher's A House With Good Bones is a contemporary Southern Gothic from a master of modern horror that explores the deep, dark roots of family and in which grandma's ghost haunting your house may be the least of your worries. In this ordinary North Carolina suburb, family secrets are always in bloom. Samantha Montgomery pulls into the driveway of her family home to find a massive black vulture perched on the mailbox, staring at the house. Inside, everything has changed. Gone is the eclectic warmth Sam expects; instead the walls are a sterile white. Now, it's very important to say grace before dinner, and her mother won't hear a word against Sam's long-dead and little-missed grandmother, who was the first to put down roots in this small southern town. The longer Sam stays, the stranger things get. And every day, more vultures circle overhead... "I was compelled to read the book in one breathless, white-knuckled sitting. Vultures, ladybugs, and underground children, oh my!"-Paul Tremblay, author of The Pallbearers Club "Wickedly witty, intensely scary, and a thoroughly modern take on the Southern Gothic, about thorny family secrets that refuse to stay buried."-Rachel Harrison, author of Cackle Also by T. Kingfisher Nettle & Bone What Moves the Dead"--.
"A Tom Doherty Associates Books."
New Book 2023 Spring.
Keywords: Supernatural; Horror; Mothers and daughters; North Carolina; Novels